Prevalence and awareness of Herpes Zoster Among Saudi Patients with Diabetes Mellitus, A Cross Sectional Study in Al-Ahsa, Saudi Arabia (World Journal of Current Medical and Pharmaceutical Research, 2023)
Background: Herpes zoster (HZ) is a painful vesicular rash that happens when an infection with the varicella-zoster virus in the sensory ganglia is reactivated. The incidence and severity of HZ and its complications increase with advancing age, with a marked increase after 50 years of age. In addition, diabetes mellitus has been found to be a risk factor for severe, persistent postherpetic neuralgia.Methods: This descriptive cross-sectional hospital-based study was conducted in Al-Ahsa City, Eastern Saudi Arabia, in 2023. The study population included patients with DM who visit outpatient (ambulatory care) in primary or secondary health care setting. The convenience sample included 224 participants. A validated closed-ended interview questionnaire was used to collect data. The collected data were analyzed by the SPSS program version 28, and both descriptive and inferential statistics were used.Results: The study included 224 participants, more than half (54.5%) of whom were female. The mean (SD) age of the sample was 61.1 ± 8 years. Most of the participants (97.8%) were married, and 29.0% had a secondary school education level. More than half of the participants (56.7%) had heard of HZ. Only 6.7% had been diagnosed with HZ, and 23.7% knew someone who had been diagnosed with HZ. In addition, 18.8% had been vaccinated against HZ. Most patients (80.8%) cited healthcare providers as their primary source of HZ knowledge, followed by friends/relatives (37.9%). More than half of the participants were aware of HZ (62.1%) and had a positive attitude towards HZ (55.8%) respectively. Awareness of HZ was positively correlated with a higher level of education, a high income, a short duration of diabetes, having heard of HZ, being diagnosed with HZ, knowing someone who had been diagnosed with HZ, and being vaccinated against HZ among diabetic patients.Conclusion:  The results revealed low vaccination rates and low awareness of HZ. The study recommends that education in simple language should be provided through various media to increase community awareness about HZ and its vaccine. Additionally, healthcare providers should promote and recommend HZ vaccinations for DM patients.